Individual-dependent molecular heterogeneity in human endometrial stromal cells: a potential determinant of female fertility - Umanthi Ranaraja; Eun Young Kim; D. Chanuka M. Kulatunga; Ryoung Eun Kim; Jin Woo Ham; You Jin Kim; Young Bok Ko; Min Kyu Kim (Molecular Biology Reports, 2026)

Retinoic acid priming enhances myogenesis of bovine muscle stem cells for cultivated meat production by modulating mitochondrial function - Yingying Mao; Eun Young Kim; Seon Woong Kim; Ryoung Eun Kim; Jin Woo Ham; Min Kyu Kim (Food Research International, 2026)

Schisandrin B mitigates oxidative damage in early porcine embryos exposed to Ochratoxin A via NRF2 pathway activation - Chuang Li; Kuk Bin Ji; Eun Young Kim; Ho Yong Choi; Jae Hyeok Yoon; Xiang Zhang; Ryoung Eun Kim; Kang Sun Park; Haixing Liu; Min Kyu Kim (Animal Reproduction Science, 2025)

Vertical and seasonal variations in stable oxygen isotope ratio of living planktonic foraminifera and estimation of habitat depth in the western tropical Pacific - Tae Wook Ko; Kyung Eun Lee; Ryoung Ah Kim (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Seasonal and vertical distribution of living planktonic foraminifera in the western tropical Pacific Ocean - Ryoung Ah Kim; Kyung Eun Lee; Tae Wook Ko (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Real-Time Measurements of Relative Tidal Volume and Stroke Volume Using Electrical Impedance Tomography with Spatial Filters: A Feasibility Study in a Swine Model Under Normal and Reduced Ventilation - Geuk Young Jang; Chi Ryang Chung; Ryoung Eun Ko; Jin Young Lee; Tong In Oh; Gee Young Suh; Yongmin Kim; Eung Je Woo (Annals of Biomedical Engineering, 2023)

Calibration of the XRF-Estimated CaCO3 Content in the Western Tropical Pacific Deep-Sea Sediments - Il Taek Lee; Tae Wook Ko; Kyung Eun Lee; Si Woong Bae; Gyu Chan Hwang; Ryoung Ah Kim (Ocean Science Journal, 2022)

Correction to: Selection strategy for damping-off resistance gene by biotechnology in rice plant - Jae-Ryoung Park; Eun-Gyeong Kim; Yoon-Hee Jang; Byoung-Ju Yun; Kyung-Min Kim (Plant and Soil, 2022)

Selection strategy for damping-off resistance gene by biotechnology in rice plant - Jae-Ryoung Park; Eun-Gyeong Kim; Yoon-Hee Jang; Byoung-Ju Yun; Kyung-Min Kim (Plant and Soil, 2022)

Construction of risk assessment manual for genetically modified rice (Oryza sativa L.) - So Young Lee; Eun-Gyeong Kim; Jae-Ryoung Park; Yoon-Hee Jang; Rahmatullah Jan; Taehun Ryu; Kyung-Min Kim (Journal of Crop Science and Biotechnology, 2021)

Flow Characteristics Around Step-Up Street Canyons with Various Building Aspect Ratios - Soo-Jin Park; Jae-Jin Kim; Wonsik Choi; Eun-Ryoung Kim; Chang-Keun Song; Eric R. Pardyjak (Boundary-Layer Meteorology, 2020)
We investigate the flow characteristics around step-up street canyons with various building aspect ratios (ratio of along-canyon building length to street-canyon width, and upwind building height to downwind building height) using a computational fluid dynamics (CFD) model. Simulated results are validated against experimental wind-tunnel results, with the CFD simulations conducted under the same building configurations as those in the wind-tunnel experiments. The CFD model reproduces the measured in-canyon vortex, rooftop recirculation zone above the downwind building, and stagnation point position reasonably well. We analyze the flow characteristics, focusing on the structural change of the in-canyon flows and the interaction between the in- and around-canyon flows with the increase of building-length ratio. The in-canyon flows undergo development and mature stages as the building-length ratio increases. In the development stage (i.e., small building-length ratios), the position of the primary vortex wanders, and the incoming flow closely follows both the upstream and downstream building sidewalls. As a result, increasing momentum transfer from the upper layer contributes to a momentum increase in the in-canyon region, and the vorticity in the in-canyon region also increases. In the mature stage (i.e., large building-length ratios), the primary vortex stabilizes in position, and the incoming flow no longer follows the building sidewalls. This causes momentum loss through the street-canyon lateral boundaries. As the building-length ratio increases, momentum transfer from the upper layer slightly decreases, and the reverse flow, updraft, and streamwise flow in the in-canyon region also slightly decrease, resulting in vorticity reduction.

Overexpression of Telomerase Reverse Transcriptase Induces Autism-like Excitatory Phenotypes in Mice - Ki Chan Kim; Jeehae Rhee; Jong-Eun Park; Dong-Keun Lee; Chang Soon Choi; Ji-Woon Kim; Han-Woong Lee; Mi-Ryoung Song; Hee Jeong Yoo; ChiHye Chung; Chan Young Shin (Molecular Neurobiology, 2016)